ANALISIS KINERJA DOSEN DALAM BIDANG PENELITIAN MENGGUNAKAN METODE SMART - Sumiyatun; Cuk Subiyantoro (LPPM STMIK El Rahma Yogyakarta, 2021)
The main task of the Tri Dharma Perguruan Tinggi lecturers, one of which is to carry out research. At STMIK AKAKOM, lecturer research can be carried out independently or in groups with funding sources from independent, internal universities and grants from the government. After conducting the research, they are required to do publications in the form of journals, research seminars, IPR and other outputs. To see the performance of lecturers in the field of research, analysis is necessary. The analysis of the decision support system developed in this study uses the Simple Multi Attribute Rating Technique (SMART) method. Aspects used as employee performance criteria include the number of research funded, the amount of funds received, the number of national journal outputs, the number of international journal outputs, the number of national seminar outputs, the number of international seminar outputs, the number of intellectual property rights. The result of this research is a program used to analyze the performance of lecturers in the research field.